COVID-19 may have increased global support for universal health coverage: multi-country observational study - Nisa, Claudia F.; Yan, Xiaoxi; Chakraborty, Bibhas; Leander, Pontus; Bélanger, Jocelyn J. (Frontiers in Public Health, 2023)
The multiple risks generated by the COVID-19 pandemic intensified the debate about healthcare access and coverage. Whether the burden of disease caused by the coronavirus outbreak changed public opinion about healthcare provision remains unclear. Here, it was specifically examined if the pandemic changed support for governmental intervention in healthcare -as a proxy to support for universal health coverage (UHC). It was also examined which psychological factors related to the socioeconomic interdependence exposed by the pandemic may be associated with a potential change. Methods: Online survey data was collected over 18-month (from March 2020 to August 2021) across 68 countries, containing various social attitudes and risk perceptions related to COVID-19. This was a convenience sample composed of voluntary participants (N=3176; age 18 and above). Results: Results show that support for government intervention in healthcare increased across geographical regions, age and gender groups (average increase 39%), above support for government intervention in other social welfare issues. Factors related to socioeconomic interdependence predicted an increased support for government intervention in healthcare, namely social solidarity (ß =.14 p<.0001), and risk to economic livelihood (ß =.09 p<.0001). Trust in the government to deal with COVID-19 decreased over time, and this negative trajectory predicted a demand for better future government intervention in healthcare (ß =-.10 p=.0003).The COVID-19 pandemic may have been a potential turning point in the global public support for UHC, as evidenced by a higher level of consensus that governments should be guarantors of healthcare.